Proline Homeostasis in Saccharomyces cerevisiae: How Does the Stress-Responsive Transcription Factor Msn2 Play a Role? - Mat Nanyan, Noreen Suliani binti; Takagi, Hiroshi (Frontiers in Genetics, 2020)
Overexpression of the stress-responsive transcription factor gene MSN2 is well known to increase the tolerance of the yeast Saccharomyces cerevisiae cells to a wide variety of environmental stresses. Recent studies have found that the Msn2 is a feasible potential mediator of amino acid homeostasis in yeast. This result is based on the finding that overexpression of the MSN2 gene exacerbates the cytotoxicity to yeast of various amino acid analogues whose uptake is increased by inhibition of the endocytic degradation of amino acid permeases as a result of a dysfunctional deubiquitination process. Increased understanding of the cellular responses induced by the Msn2-mediated amino acid incorporation will provide better comprehension of how cells respond to and counteract to different kinds of stimuli and will also contribute to the breeding of industrial yeast strains with increased productivity.